2006
DOI: 10.1007/s10562-006-0075-1
|View full text |Cite
|
Sign up to set email alerts
|

Selective Hydrogenation of Benzene to Cyclohexene Over Colloidal Ruthenium Catalyst Stabilized by Silica

Abstract: A colloidal ruthenium catalyst stabilized by silica was prepared through microemulsion processing. Ruthenium colloids with particle size about 4 nm are highly dispersed in silica. The selective hydrogenation of benzene to cyclohexene was studied over the catalyst. Much higher activity and selectivity was obtained compared with its supported counterparts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 30 publications
2
36
0
2
Order By: Relevance
“…8a. It is well considered that higher dispersion of ruthenium leads to higher hydrogenation activity, as well as the improvement of cyclohexene selectivity for the catalyst calcined at lower temperature due to the small size of ruthenium crystallite [26]. Notably, the slight decrease of the selectivity at lower temperature in our work could be explained by the higher concentration of cyclohexene in the oil phase, which led to enhanced mass transfer of cyclohexene from the oil phase to catalyst surface and sacrificed the beneficial effect of the small grain size on the selectivity.…”
Section: Effect Of the Calcination Temperature Of Ruthenium Catalystmentioning
confidence: 99%
“…8a. It is well considered that higher dispersion of ruthenium leads to higher hydrogenation activity, as well as the improvement of cyclohexene selectivity for the catalyst calcined at lower temperature due to the small size of ruthenium crystallite [26]. Notably, the slight decrease of the selectivity at lower temperature in our work could be explained by the higher concentration of cyclohexene in the oil phase, which led to enhanced mass transfer of cyclohexene from the oil phase to catalyst surface and sacrificed the beneficial effect of the small grain size on the selectivity.…”
Section: Effect Of the Calcination Temperature Of Ruthenium Catalystmentioning
confidence: 99%
“…In recent years, great progress has been made in this field. Ning et al 6 prepared Ru-SiO 2 catalysts by microemulsion processing and obtained a maximum cyclohexene yield of 42%. Liu et al 7 prepared a Ce-promoted Ru/SBA-15 catalyst by a "two solvents" impregnation method and achieved a cyclohexene yield of 53.8%.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the increased levels of partially hydrogenated products were due in part to the higher solubility of the diene relative to the monoene in the IL, which results in its spontaneous elimination from the catalyst phase [34]. Partial reduction of benzene also has been reported using nanoparticle catalysts in ILs [35,36]. Because far more active catalysts are required to hydrogenate arenes compared with alkenes, by virtue of the need to break the aromaticity, suppressing further hydrogenation is a considerable challenge and results in somewhat lower selectivity toward the partial hydrogenation product compared with dienes; for example, cyclohexadiene can be converted to cyclohexene with a selectivity of 96% with high conversion [31].…”
Section: Hydrogenation Of Benzene and Arene Derivativesmentioning
confidence: 99%